Recent Advances in Asymmetric Transformations of Unactivated Alkanes and Cycloalkanes through Direct C—H Functionalization - Cheng, Shiyan; Li, Qianyu; Cheng, Xiuliang; Lin, Yu‐Mei; Gong, Lei (Chinese journal of chemistry, 2022)
Comprehensive Summary The direct conversion of unactivated alkanes and cycloalkanes into structurally diverse molecules through aliphatic C—H functionalization is a useful process, which has attracted intense interest from academia and industry. Methods to control chemo‐ and site‐selectivity, combined with asymmetric catalysis, provide appealing access to high value‐added enantiomer‐enriched compounds but are far less developed. This review focuses on recent progress in (i) asymmetric reactions of alkanes or cycloalkanes with prochiral substrates which generate a stereocenter adjacent to the cleaved C(sp3)–H bond, and (ii) C(sp3)–H enantiodiscriminatory reactions creating a new stereogenic center on the carbon of a cleaved C(sp3)–H bond. Elegant strategies are discussed, including (a) metal carbene‐induced C—H insertions by chiral rhodium catalysts, (b) metal‐oxo‐mediated C—H oxidation by biomimetic manganese catalysts, (c) enzyme catalysis by cytochromes P450 variants, and (d) dual catalysis by a photocatalyst and a chiral Lewis acid (CLA) or a chiral phosphoric acid (CPA). These catalytic systems can not only precisely recognize primary, secondary and tertiary C—H bonds at specific positions in alkanes and cycloalkanes, but also support a high level of stereoselectivity in the reactions. It is expected that the advances will stimulate further progress in asymmetric catalysis, synthetic methodology, pharmaceutical development and industrial processes. Recent studies on asymmetric synthesis through direct and selective C—H functionalization of alkanes and cycloalkanes, based on metal carbene‐induced C—H insertions by chiral rhodium catalysts, metal‐oxo‐mediated C—H oxidation by biomimetic manganese catalysts, enzyme catalysis by cytochromes P450 variants, and dual catalysis by a photocatalyst and a chiral Lewis acid (CLA) or a chiral phosphoric acid (CPA), are summarized and discussed.